If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x + -3)(y + 200) = 7200 Reorder the terms: (-3 + x)(y + 200) = 7200 Reorder the terms: (-3 + x)(200 + y) = 7200 Multiply (-3 + x) * (200 + y) (-3(200 + y) + x(200 + y)) = 7200 ((200 * -3 + y * -3) + x(200 + y)) = 7200 ((-600 + -3y) + x(200 + y)) = 7200 (-600 + -3y + (200 * x + y * x)) = 7200 (-600 + -3y + (200x + xy)) = 7200 Reorder the terms: (-600 + 200x + xy + -3y) = 7200 (-600 + 200x + xy + -3y) = 7200 Solving -600 + 200x + xy + -3y = 7200 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '600' to each side of the equation. -600 + 200x + xy + 600 + -3y = 7200 + 600 Reorder the terms: -600 + 600 + 200x + xy + -3y = 7200 + 600 Combine like terms: -600 + 600 = 0 0 + 200x + xy + -3y = 7200 + 600 200x + xy + -3y = 7200 + 600 Combine like terms: 7200 + 600 = 7800 200x + xy + -3y = 7800 Add '3y' to each side of the equation. 200x + xy + -3y + 3y = 7800 + 3y Combine like terms: -3y + 3y = 0 200x + xy + 0 = 7800 + 3y 200x + xy = 7800 + 3y Reorder the terms: -7800 + 200x + xy + -3y = 7800 + 3y + -7800 + -3y Reorder the terms: -7800 + 200x + xy + -3y = 7800 + -7800 + 3y + -3y Combine like terms: 7800 + -7800 = 0 -7800 + 200x + xy + -3y = 0 + 3y + -3y -7800 + 200x + xy + -3y = 3y + -3y Combine like terms: 3y + -3y = 0 -7800 + 200x + xy + -3y = 0 The solution to this equation could not be determined.
| -3x-6=4x+15 | | 19x=9x+68 | | 2x9/3=8-3x | | (6-9)(9-10)(40-50)=6 | | -2x*x+4x+30=0 | | 10.24=y/4 | | 5(x-3)+2(x+2)=50 | | 3e^3+72e=33e^2 | | 36=5y+4y | | j^2-2=17 | | i^2+6=6 | | 180=21+x-1 | | g(x)=x-14 | | 2y=10x-7 | | 10t-28=12t-52 | | 180=42+8+x | | 3w+7+9w= | | 27+7c=150+c | | 13h^2-3=4209 | | 7s+4s=-72 | | -3x*x-75=0 | | 7+6n=37 | | 42-2r=165-3r | | 2a=a+44 | | 12-5u=-15 | | 6(v-4)-8v=-20 | | 2y+6(y+2)=-36 | | x=5-1/x | | 0.2x-0.4(5-x)=0.7 | | x*x-23=52-2*x*x | | 5m-4=41 | | 1/x=5-x |